2016
DOI: 10.20960/nh.267
|View full text |Cite
|
Sign up to set email alerts
|

Asociación del polimorfi smo TNF-alpha -308 G/A con los cambios metabólicos secundarios a una dieta hipocalórica rica en proteínas/baja en hidratos de carbono versus una dieta hipocalórica estándar

Abstract: Palabras clave:Polimorfi smo G308 TNF-alpha. Dieta hipocalórica. Obesidad. ResumenAntecedentes: los diferentes estudios genéticos han identifi cado un cambio G-> A en la región promotora del gen de TNF-alfa en la posición -308 (rs1800629). Objetivo: el objetivo de nuestro estudio fue investigar la infl uencia del polimorfi smo en -308 GA del gen TNF-alfa en la respuesta metabólica y la pérdida de peso secundarias a dos dietas hipocalóricas. Método: una muestra de 283 sujetos obesos fue evaluada en forma prospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…It has also been suggested that eating habits might influence these genes’ effects on obesity-related traits. Few studies have described the impact of different hypocaloric diets on weight loss and metabolic parameters, analyzing the rs1800629 polymorphism of TNF-α in obese participants [25,26]. Therefore, analyzing and understanding the influence of genetic markers on the effects of training protocols, as proposed by our study, may support the development of new perspectives not only on individualization of exercise programs to make them more efficient and safer, but also on improved recovery, traumatology, medical care, diet, supplementation and many other areas [3].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested that eating habits might influence these genes’ effects on obesity-related traits. Few studies have described the impact of different hypocaloric diets on weight loss and metabolic parameters, analyzing the rs1800629 polymorphism of TNF-α in obese participants [25,26]. Therefore, analyzing and understanding the influence of genetic markers on the effects of training protocols, as proposed by our study, may support the development of new perspectives not only on individualization of exercise programs to make them more efficient and safer, but also on improved recovery, traumatology, medical care, diet, supplementation and many other areas [3].…”
Section: Discussionmentioning
confidence: 99%